IMPROVEMENT ALGORITHM OF TIME-VARYING MESHING STIFFNESS OF HELICAL GEAR AND ANALYSIS OF INFLUENCING FACTORS - WU LuJi; YANG ShiHao; FENG Wei; YANG LinJie (Jixie qiangdu)
An improved calculation method for the time-varying mesh stiffness of helical gear was proposed based on the potential energy method and the slice integration principle, taking into account the transition curve equation of tooth root. This method considered the parameter equation of the transition curve of the real tooth root, corrected the integral interval of the involute tooth profile, and compared with the finite element method to verify the validity of the algorithm and reduce the calculation error of the time-varying mesh stiffness. The influence of tooth width, helix angle, tooth number and modulus on the time-varying mesh stiffness was analyzed based on this method. The results show that the average time-varying mesh stiffness is greatly affected by the tooth width, exhibiting an approximate linear relation. In contrast, it is less influenced by the helix angle and number of teeth. As the helix angle increases, the average value fluctuates in a small range. When the center distance is fixed, as the number of teeth increases, the time-varying mesh stiffness slowly increases. Moreover, changes in gear parameters affect the contact ratio. Notably .when the axial contact ratio is an integer, the fluctuation of time-varying mesh stiffness is relatively small.